Ações educativas não formais como potencializadoras de desenvolvimento na agricultura familiar: o caso do programa sucessão rural familiar - Martinelli, Alini Cossul (My University, 2023)
This dissertation investigated the Family Rural Succession Program, from Cooperativa Sicredi Pioneira _ RS, as a non-formal education action, seeking to understand the reality experienced by the subjects and their families and understand the impact of the educational actions provided by the Program, regarding the development of family farming. The methodology used was document analysis, bibliographical research and semi-structured interviews, with open questions and observation in five participating families, and two employees of the Cooperative. The theoretical support has the support of Maria da Glória Gohn, when she deals with formal education, informal education and non-formal education, as well as Paulo Freire when we evidence the transformation that education can bring to the lives of subjects. The research made it possible to recognize the importance and seriousness of non-formal education for adults, taking into account that it is guided by objectives and with intentionality, creating possibilities for the construction of knowledge and the promotion of an autonomous subject, which emerges as a basic premise for the social transformation and consolidation of a more prosperous society. [resumo fornecido pelo autor]
A presente dissertação investigou o Programa Sucessão Rural Familiar, da Cooperativa Sicredi Pioneira - RS, como uma ação de educação não formal, buscando compreender a realidade vivida pelos sujeitos e suas famílias e entender qual o impacto das ações educativas proporcionadas pelo Programa, quanto ao desenvolvimento da agricultura familiar. A metodologia utilizada foi análise documental, pesquisa bibliográfica e entrevistas semiestruturadas, com perguntas abertas e observação em cinco famílias participantes, e dois funcionários da Cooperativa. O suporte teórico, conta com o apoio de Maria da Glória Gohn, quando esta trata de educação formal, educação informal e educação não formal, bem como em Paulo Freire quando evidenciamos a transformação que a educação pode trazer para a vida dos sujeitos. A pesquisa possibilitou reconhecer a importância e seriedade da educação não formal para adultos, levando em conta que é norteada por objetivos e com intencionalidade, criando possibilidades para a construção do conhecimento e a promoção de um sujeito autônomo, o que desponta como premissa básica para a transformação social e consolidação de uma sociedade mais próspera. [resumo fornecido pelo autor]
Keywords: Educação não-formal; Educação de adultos; Agricultura familiar; SICREDI (Organização); Cooperativismo; Non-formal education; Elementary education of adults; Family farms; Cooperation